MspI restriction enzyme evidence moderate polymorphism in the second exon of BoLA-DRB3 gene - Giovambattista, Guillermo (2003)
At present, 53 PCR-RFLP alleles of the bovine DRB3 exon 2 were reported. In order to analyse the putative MspI restriction patterns present in the exon 2 of BoLA-DRB3 gene, all available DNA sequences were retrieved from Genbank Data Library. In this analysis, two MspI restriction sites and five restriction patterns were found. In addition, the observed restriction patterns obtained after MspI digestion of genomic DNA were compared with those predicted from the DRB3 DNA sequence analysis. The use of MspI restriction enzymes together with BstYI, HaeIII and RsaI could be useful in recognising some sequences differences in a single PCR-RFLP allele as defined by the previously used combination of enzyme, improving the robustness of this typing method designed by van Eijk et al. (1992). Despite the number of restriction patterns detected by MspI and BstYI are similar, the MspI patterns are more easily identified than those of BstYI. MspI enzyme works well in the same reaction buffer and temperature as HaeIII and RsaI, thus simplifying double digestions. Finally, the costs may be reduced.